Koncepcje federacyjne podziemnej „Unii” (1940-1945): w poszukiwaniu polskiego wzorca integracji europejskiej (Politeja, 2019)
The article aims at identifying and analysing the particularities of the federalist ideas of Polish clandestine catholic organisation the Union. In 1943 the group merged with the Christian-democratic Labour Party (SP) becoming its ideological centre. Throughout the Second World War the Union produced a series of programmatic documents and clandestine press where it discussed the shape of future Europe which was to become a pan-federation of regional federations cemented by the common values and principles enshrined in Christianity which were the foundations of Western civilization. In elaborating future plans for Europe, the Union drew explicitly from the memory of the Polish-Lithuanian Commonwealth setting it as an example for modern Poland and other European States. Historical Poland was perceived not just as a state but as a “normative power”, this was possible because the Union rejected the modern, ‘westphalian’ concept of state. Instead it advocated creation of a pluralistic federation of nations bound together by common values, where national egoisms were mitigated by common Christian values.